From Engagement to Containment? Perubahan Politik Luar Negeri Amerika Serikat Terhadap Tiongkok - -, Muhammad Erza Pradana (Universitas Sulawesi Barat, 2023)
This study examines the dynamics of changes in the United States' foreign policy towards the People's Republic of China (PRC). The United States now sees China as a potential competitor attempting to dominate Asia. The logic of the neorealist theory in general and offensive realism in particular explains that the main US national interest is to prevent other countries from becoming regional hegemons. Therefore, the rational foreign policy aim of the US is to contain the PRC. Looking back in history, however, containment was not the first policy implemented by the United States. Using the theory of neorealism as a tool of analysis, this study concludes that the structure of the international system and the distribution of power are the main factors in the dynamics of changes in US foreign policy towards China. However, by using neorealism theory, the research does not emphasize domestic factors that shape foreign policy, although non-structural factors will be briefly explained. This research was conducted using qualitative methods. The data used were collected through library research.